Penggunaan Metode Eksperimen Dalam Pembelajaran Sains Di TK As-Sunnah - Novi Sri Handayani; Rikha Surtika Dewi (UIN Sultan Maulana Hasanudin Banten, 2023)
Science-based early childhood education can greatly enhance a child's development. They can actively participate in scientific research and experiments, which garners their creativity and curiosity. Researchers used the PTK approach in this study. As-Sunnah Kindergarten in Tasikmalaya City served as the location for this research, which was carried out from April to May 2023. The results of the research are presented in a narrative format based on a study of various sources, including books, journals, and others. material that is relevant to the problem and subject matter regarding the experimental method. Findings from observations also revealed that the majority of children were able to show reactions such as worry, joy, curiosity, spontaneousness, and not giving up easily.